Contracting Strategies for Arthroplasty—Bundles to Population Health - Jacofsky, David J.; Jawin, Paul; Walton, Geoff; Fraser, Lisa (The Journal of Knee Surgery, 2017)
Orthopedics, and especially total joint replacement (TJR), is growing in payer prominence due to large projected increases in volume. The unsustainability of the fee-for-service payment system has lead Centers for Medicare and Medicaid Services to employ new value and risk-based contracting strategies on a population health basis and on an episode of care basis, with programs such as the Bundled Payment for Care Improvement program and the Comprehensive Care for Joint Replacement program. These trends are forcing hospitals and physicians to align to improve quality and reduce costs through new structures such as Accountable Care Organizations, comanagement programs, and gainsharing. Bundled payment programs are typically used to align specialists such as orthopedic surgeons and TJR has been on the forefront of bundled payment contracting strategies. Bundled payment programs with commercial insurers can create additional opportunities, as do commercial bundled payment contracts for TJR performed on an outpatient basis. As these programs are now becoming mandatory, surgeons must understand the structural aspects of these arrangements and the levers available to optimize the likelihood of success.
Keywords: knee arthroplasty; contracting; bundled payments; population health; Affordable Care Act